Exhibiting of geospatial attribute data using popup template Java-script application programming interface - Harish, Ballu; Dwiwedi, R. S. (International Journal of Scientific Reports, 2020)
Arc-GIS server is used in creating web, desktop, mobile applications. Arc-GIS for server provides end user applications and services for spatial data management, visualization and spatial analysis. The proposed work deals with exhibiting of geo-spatial attribute data using the facility of Java script application programme interfaces (API’s) from Arc-GIS server. Popup-layout API reference is utilized in the work and furthermore two of its properties are utilized relying upon the need of the work. All the programming interfaces have their advantages for encouraging clients work to connect with the geo-spatial information. Keen web maps make an extraordinary method of envisioning complex data. They assist with beating up apparently disconnected data, uncover concealed examples, mine enormous datasets. Information can be composed on the work area, sent to the cloud, and shared utilizing Arc-GIS server on the web.